"Recovery Came First": Desistance versus Recovery in the Criminal Careers of Drug-Using Offenders. (30th December 2012) - Colman, Charlotte; Vander Laenen, Freya
Abstract : The aim of our paper is to gain insight in the desistance process of drug-using offenders. We explore the components of change in the desistance process of drug-using offenders by using the cognitive transformation theory of Giordano et al. as a theoretical framework. The desistance process of drug-using offenders entails a two-fold process: desistance of criminal offending and recovery. The results however indicate that desistance is subordinate to recovery because of the fact that drug-using offenders especially see themselves as drug users and not as "criminals." Their first goal was to start recovery from drug use. They were convinced that recovery from drug use would lead them to a stop in their offending. In the discussion, we explore the implications of this result for further research.